PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN TRANSAKSIONAL TERHADAP KINERJA PEGAWAI DI HARIAN WASPADA MEDAN - Asnora, Fazhil Hanafi (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2019)
This study is based on the idea that transformational and transactional leadership style is very important for employees because job satisfaction is achieved with good cause employees are willing and motivated to provide a positive influence on the success of the organization that supports organizational goals effectively and efficiently. Therefore, this study aims to determine whether the transformational and transactional leadership styles simultaneously significant effect on employee performance. The theory is used to analyze the problems is about transformational leadership, transactional leadership style, employee performance. This research was conducted in the Harian Waspada Medan, especially in the civil service. Research approach is a quantitative approach to the type of associative research. The results obtained and also become keseimpulan this study include that the transformational leadership style has no significant effect on employee performance. While transactional leadership style variables have a significant effect on employee performance. Variable transformational and transactional leadership styles simultaneously significant effect on employee performance.